Speleothem evidence of late glacial and Early Holocene Preboreal and Boreal hydro-climate changes in western Mediterranean (Corchia Cave, Italy) - Andrea Columbu; Ilaria Isola; Giovanni Zanchetta; Russell N. Drysdale; Stefano Natali; John C. Hellstrom; Michel Magny; Anthony E. Fallick (Quaternary Science Reviews, 2025)

Origin of the Mizab barite vein-type deposit, Ain Mimoun (NE Algeria): evidence from fluid inclusion and S-, O- and C-stable isotope studies - Rabah Zedam; Rabah Laouar; Abdelmalek Lekoui; Houssem Metrouni; Salah Bouhlel; Adrian J. Boyce; Anthony E. Fallick (Arabian Journal of Geosciences, 2022)

Correction to: Beyond one-way determinism: San Frediano’s miracle and climate change in Central and Northern Italy in late antiquity - Giovanni Zanchetta; Monica Bini; Kevin Bloomfield; Adam Izdebski; Nicola Vivoli; Eleonora Regattieri; Ilaria Isola; Russell N. Drysdale; Petra Bajo; John C. Hellstrom; Robert Wiśniewski; Anthony E. Fallick; et al. (Climatic Change, 2021)

Fluid and metal sources in the Fäboliden hypozonal orogenic gold deposit, Sweden - Glenn Bark; Adrian J. Boyce; Anthony E. Fallick; Pär Weihed (Mineralium Deposita, 2021)
To model the formation of orogenic gold deposits, in a global perspective, it is important to understand the ore-forming conditions not only for deposits hosted in greenschist facies rocks but also in amphibolite facies. The Paleoproterozoic Fäboliden deposit in northern Sweden belongs to the globally rare hypozonal group of orogenic gold deposits and, as such, constitutes a key addition to the understanding of amphibolite facies orogenic gold deposits. The Fäboliden deposit is characterized by auriferous arsenopyrite-rich quartz veins, hosted by amphibolite facies supracrustal rocks and controlled by a roughly N-striking shear zone. Gold is closely associated with arsenopyrite-löllingite and stibnite, and commonly found in fractures and as inclusions in the arsenopyrite-löllingite grains. The timing of mineralization is estimated from geothermometric data and field relations at c. 1.8 Ga. In order to constrain the origin of gold-bearing fluids in the Fäboliden deposit, oxygen, hydrogen, and sulfur isotope studies were undertaken. δ 18 O from quartz in veins shows a narrow range of + 10.6 to + 13.1‰. δD from biotite ranges between − 120 and − 67‰, with most data between − 95 and − 67‰. δ 34 S in arsenopyrite and pyrrhotite ranges from − 0.9 and + 3.6‰ and from − 1.5 and + 1.9‰, respectively. These stable isotope data, interpreted in the context of the regional and local geology and the estimated timing of mineralization, suggest that the sulfur- and gold-bearing fluid was generated from deep-crustal sedimentary rocks during decompressional uplift, late in the orogenic evolution of the area. At the site of gold ore formation, an 18 O-enriched magmatic fluid possibly interacted with the auriferous fluid, causing precipitation of Au and the formation of the Fäboliden hypozonal orogenic gold deposit.

Beyond one-way determinism: San Frediano’s miracle and climate change in Central and Northern Italy in late antiquity - Giovanni Zanchetta; Monica Bini; Kevin Bloomfield; Adam Izdebski; Nicola Vivoli; Eleonora Regattieri; Ilaria Isola; Russell N. Drysdale; Petra Bajo; John C. Hellstrom; Robert Wiśniewski; Anthony E. Fallick; et al. (Climatic Change, 2021)
Integrating palaeoclimatological proxies and historical records, which is necessary to achieve a more complete understanding of climate impacts on past societies, is a challenging task, often leading to unsatisfactory and even contradictory conclusions. This has until recently been the case for Italy, the heart of the Roman Empire, during the transition between Antiquity and the Middle Ages. In this paper, we present new high-resolution speleothem data from the Apuan Alps (Central Italy). The data document a period of very wet conditions in the sixth c. AD, probably related to synoptic atmospheric conditions similar to a negative phase of the North Atlantic Oscillation. For this century, there also exist a significant number of historical records of extreme hydroclimatic events, previously discarded as anecdotal. We show that this varied evidence reflects the increased frequency of floods and extreme rainfall events in Central and Northern Italy at the time. Moreover, we also show that these unusual hydroclimatic conditions overlapped with the increased presence of “water miracles” in Italian hagiographical accounts and social imagination. The miracles, performed by local Church leaders, strengthened the already growing authority of holy bishops and monks in Italian society during the crucial centuries that followed the “Fall of the Roman Empire”. Thus, the combination of natural and historical data allows us to show the degree to which the impact of climate variability on historical societies is determined not by the nature of the climatic phenomena per se, but by the culture and the structure of the society that experienced it.

The oceanic anoxic event 2 at Es Souabaa (Tebessa, NE Algeria): bio-events and stable isotope study - Sihem Salmi-Laouar; Bruno Ferré; Khoudair Chaabane; Rabah Laouar; Adrian J. Boyce; Anthony E. Fallick (Arabian Journal of Geosciences, 2018)

Mineralogy, alteration patterns, geochemistry, and fluid properties of the Ag-Au epithermal deposit Nová Baňa, Slovakia - Juraj Majzlan; Khulan Berkh; Stefan Kiefer; Peter Koděra; Anthony E. Fallick; Martin Chovan; František Bakos; Adrián Biroň; Štefan Ferenc; Jaroslav Lexa (Mineralogy and Petrology, 2018)

The role of evaporites in the formation of gems during metamorphism of carbonate platforms: a review - Gaston Giuliani; Jean Dubessy; Daniel Ohnenstetter; David Banks; Yannick Branquet; Julien Feneyrol; Anthony E. Fallick; Jean-Emmanuel Martelat (Mineralium Deposita, 2018)

Tissue-specific fatty acid profiles of vent-obligate tonguefishes (Symphurus spp.) on volcanic arcs in the western Pacific Ocean - Catherine J. Stevens; David W. Pond; Anthony E. Fallick; S. Kim Juniper (Marine Biology, 2016)

Sulphur stable isotope systematics in diagenetic pyrite from the North Sea hydrocarbon reservoirs revealed by laser combustion analysis - Anthony E. Fallick; Adrian J. Boyce; Paul McConville (Isotopes in Environmental and Health Studies, 2012)

18O/16O and V/Cr ratios in gem tsavorites from the Neoproterozoic Mozambique metamorphic belt: a clue towards their origins? - Gaston Giuliani; Anthony E. Fallick; Julien Feneyrol; Daniel Ohnenstetter; Vincent Pardieu; Mark Saul (Mineralium Deposita, 2011)

Stable isotopes reveal Holocene changes in the diet of Adélie penguins in Northern Victoria Land (Ross Sea, Antarctica) - Sandra Lorenzini; Carlo Baroni; Anthony E. Fallick; Ilaria Baneschi; Maria Cristina Salvatore; Giovanni Zanchetta; Luigi Dallai (Oecologia, 2010)

Formation of the Vysoká–Zlatno Cu–Au skarn–porphyry deposit, Slovakia - Peter Koděra; Jaroslav Lexa; Anthony E. Fallick (Mineralium Deposita, 2010)

Early‐middle Holocene land snail shell stable isotope record from Grotta di Latronico 3 (southern Italy) - André C. Colonese; Giovanni Zanchetta; Elisabeth Dotsika; Russell N. Drysdale; Anthony E. Fallick; Renata Grifoni Cremonesi; Giuseppe Manganelli (Journal of Quaternary Science, 2010)
This paper compares stable isotope (δ 18 O and δ 13 C) records of early–middle Holocene land snail shells from the archaeological deposits of Grotta di Latronico 3 (LTR3; southern Italy) with modern shell isotopic data. No substantial interspecific variability was observed in shell δ 18 O (δ 18 Os) of modern specimens ( Pomatias elegans , Cornu aspersum , Eobania vermiculata , Helix ligata and Marmorana fuscolabiata ). In contrast, interspecific shell δ 13 C (δ 13 Cs) variability was significant, probably due to different feeding behaviour among species. The δ 18 Os values of living land snails suggest that species hibernate for a long period during colder months, so that the signal of 18 O‐depleted winter rainfall in their δ 18 Os is lost. This suggests that δ 18 Os and δ 13 Cs values of Pomatias elegans from this archaeological succession provide valuable clues for seasonal (spring–autumn) climatic conditions during the early–middle Holocene. The δ 18 Os values of fossil specimens are significantly lower than in modern shells and in agreement with other palaeoclimatic records, suggesting a substantial increase of precipitation and/or persistent changes in air mass source trajectories over this region between ca. 8.8 cal ka BP and 6.2–6.7 ka ago. The δ 13 Cs trend suggests a transition from a slightly 13 C‐enriched to a 13 C‐depleted diet between early and middle Holocene compared to present conditions. We postulate that this δ 13 Cs trend might reflect changes in the C3 vegetation community, potentially combined with other environmental factors such as regional moisture increase and the progressive decrease of atmospheric CO 2 concentration. Copyright © 2010 John Wiley & Sons, Ltd.

Carbon and nitrogen cycling pursuant to the great oxidation event: Evidence from the paleoproterozoic of fennoscandia - Lee Kump; Christopher Junium; Michael Arthur; Alex Brasier; Anthony Fallick; Victor Melezhik; Aivo Lepland; Alenka Črne; Genming Luo (Journal of Earth Science, 2010)

Environmental change in northern Belize since the latest Pleistocene - Sarah Metcalfe; Ann Breen; Malcolm Murray; Peter Furley; Anthony Fallick; Angus McKenzie (Journal of Quaternary Science, 2009)
Cores from the New River Lagoon in Belize have been analysed using a range of palaeolimnological proxies to reconstruct change since the latest Pleistocene. The combination of diatom and stable isotope analyses (supported by mineralogical and major element data) indicate that the New River Lagoon has been a freshwater system throughout the period of record. For most of this time the lagoon has been hydrologically open, but there are indications that it may have become closed in the latest Pleistocene or very early Holocene. This may have been associated with a drier climate and lower sea level. Mid‐Holocene records are consistent with those from elsewhere in the region, indicating a stable and moist climate. The late Holocene was marked by greater variability, but there is no clear evidence of any drying in the late Classic coincident with the Maya ‘collapse’ ca. AD 900. Our results indicate that the continuity of occupation at the Maya site of Lamanai on the shores of the New River Lagoon is consistent with continued access to freshwater during periods of regional climatic variability. The importance of conditions at individual sites when considering both system response and human vulnerability to climate change is emphasised. Copyright © 2009 John Wiley & Sons, Ltd.

Oxygen isotopes composition of sapphires from the French Massif Central: implications for the origin of gem corundum in basaltic fields - Gaston Giuliani; Anthony Fallick; Daniel Ohnenstetter; Guy Pegere (Mineralium Deposita, 2009)

Geology, fluid inclusion and sulphur isotope characteristics of the El Cobre VHMS deposit, Southern Cuba - Xiomara Cazañas; Pura Alfonso; Joan Carles Melgarejo; Joaquín Antonio Proenza; Anthony Edward Fallick (Mineralium Deposita, 2008)

Late Quaternary palaeohydrology of Lake Pergusa (Sicily, southern Italy) as inferred by stable isotopes of lacustrine carbonates - Giovanni Zanchetta; Alessandra Borghini; Anthony E. Fallick; Francesco P. Bonadonna; Gabriello Leone (Journal of Paleolimnology, 2007)

Oxygen isotope systematics of gem corundum deposits in Madagascar: relevance for their geological origin - Gaston Giuliani; Anthony Fallick; Michel Rakotondrazafy; Daniel Ohnenstetter; Alfred Andriamamonjy; Théogène Ralantoarison; Saholy Rakotosamizanany; Marie Razanatseheno; Yohann Offant; Virginie Garnier; Christian Dunaigre; Dietmar Schwarz; et al. (Mineralium Deposita, 2007)

Epithermal gold veins in a caldera setting: Banská Hodruša, Slovakia - Peter Koděra; Jaroslav Lexa; Andrew Hugh Rankin; Anthony Edward Fallick (Mineralium Deposita, 2005)

Source and evolution of ore-forming hydrothermal fluids in the northern Iberian Pyrite Belt massive sulphide deposits (SW Spain): evidence from fluid inclusions and stable isotopes - Javier Sánchez-España; Francisco Velasco; Adrian J. Boyce; Anthony E. Fallick (Mineralium Deposita, 2003)

Timing and genesis of base-metal mineralisation in black shales of the Upper Permian Ravnefjeld Formation, Wegener Halvø, East Greenland - Mikael Pedersen; Jesper K. Nielsen; Adrian J. Boyce; Anthony E. Fallick (Mineralium Deposita, 2003)

Sulphur isotope composition of Silurian shale-hosted PGE-Ag-Au-Zn-Cu mineralisations of the Prades Mountains (Catalonia, Spain) - Pura Alfonso; Carles Canet; Joan C. Melgarejo; Anthony E. Fallick (Mineralium Deposita, 2002)

Stable oxygen isotope and pollen records from eastern Scotland and a consideration of Late‐glacial and early Holocene climate change for Europe - GRAEME WHITTINGTON; ANTHONY E. FALLICK; KEVIN J. EDWARDS (Journal of Quaternary Science, 1996)

Stable oxygen isotope and pollen records from eastern Scotland and a consideration of Late-glacial and early Holocene climate change for Europe - GRAEME WHITTINGTON; ANTHONY E. FALLICK; KEVIN J. EDWARDS (Journal of Quaternary Science, 1996)